A critical review on advancements and challenges in CO2 gas separation via 6FDA-based membranes - Mehtab Ali, Darban; Serene Lock, Sow Mun; Suhaib Umer, Ilyas; Sharjeel, Waqas; Lim, Lam Ghai; Irene Lock, Sow Mei; Kang, Dun Yen; Mohd Hafiz Dzarfan, Othman; Yiin, Chung Loong; Noor, e Hira; Zunara, Bashir (Elsevier Ltd., 2025)
Membrane technology is at the cutting edge of gas separation, offering energy-efficient and scalable solutions across industries. This review analyses 4,4′-(hexafluoroisopropylidene) diphthalic anhydride (6FDA)-based polyimides, emphasising their vital role in CO2 gas separation. It discusses recent advancements and highlights their characteristics: high free volume, thermal stability, and chemical resistance, making them ideal for efficient gas separation. The review also covers fabrication methods for 6FDA-derived membranes, including composite and hybrid types with superior performance. It further examines recent advancements in 6FDA-based polymeric membranes, particularly mixed matrix membranes (MMMs) and hybrid architectures, with a focused discussion on polymer modifications such as thermal rearrangement and cross-linking, as well as the strategic integration of advanced fillers, including metal-organic frameworks (MOFs), zeolitic imidazolate frameworks (ZIFs), and ionic liquids (ILs). These advancements collectively contribute to enhanced membrane performance and expand their potential applications in gas separation technologies. For instance, adding 20 wt. % ZIF-67 to 6FDA-Durene significantly increased CO₂ permeability from 669.12 to 1529.86 Barrer. However, this enhancement came at the cost of a slight decrease in CO₂/N₂ and CO₂/CH₄ selectivities. In contrast, incorporating 20 wt. % [Emim][Tf₂N]@ZIF-67 improved CO₂ permeability by 33 %, while also increasing CO₂/N₂ selectivity from 25 to 28 and CO₂/CH₄ selectivity from 24 to 28. This highlights the superior performance of hybrid membranes over other composite formulations. The review highlights molecular simulations' critical role in revealing atomistic interactions and optimising filler-polymer interfaces, addressing scalability issues in experimental separations. These simulations provide insights for developing high-performance membranes. It also offers a comprehensive overview of current research and future directions by discussing experimental findings and molecular dynamics simulations. Additionally, it emphasises the potential of 6FDA-based membranes for industrial applications, indicating that advancements in filler modification and polymer design could help overcome existing challenges.